Children Should Not Be Treated Like Little Adults in the PFT Lab... includes discussion. - Seed, Laura; Wilson, David; Coates, Allan L. (Respiratory Care, 2012)
Over the years a great deal of effort has been made to standardize all pulmonary function tests on adults. Many of the "rules" concerning the interpretation of the spirogram have been based entirely on adult observations. In the age of increasing conformity, and attempts to relate "adult" literature to the pediatric population, the latter was given much less emphasis than the former. This review will attempt to show what areas in pulmonary function testing are similar in adults and children, but more specifically will show the areas that are different. The latest standards published by the American Thoracic Society/European Respiratory Society in 2005 have attempted to incorporate some differences for the pediatric population for spirometry, but more work needs to be done in this area. While it is recognized that spirometry is the primary pulmonary function test for children, there are a number of circumstances where the addition of plethysmography and lung diffusion measurements are necessary. The review will state some of the limitations of these tests when performed by children. Lung function testing, particularly spirometry, has much to offer in the diagnosis of lung disease in children and the monitoring of response to therapy. With better standardization of pulmonary function testing in children, and more trained technologists, the age limits for testing can be extended to below 6 years of age and sometimes below 5. Also with better standardization the results obtained are meaningful and when interpreted in context of age offer excellent diagnostic information to better treat the child with lung disease.